Reimagining Higher Education in Europe: Digital Learning, Research, and Global Collaboration - Ulan Susilawati, Akhmad Syahri, Ahmad Sulhan (Lembaga Bale Literasi, 2025)
This study investigates the transformation of higher education in Europe through the integration of digital learning, research innovation, and global collaboration. Using a mixed-methods approach, quantitative data were collected from 120 respondents across 20 higher education institutions, while qualitative insights were obtained from 30 semi-structured interviews. The quantitative data were analyzed using SPSS 27, and the qualitative data were coded and thematically examined with NVivo 12. The SPSS analysis revealed that digital learning accessibility (M = 4.45, SD = 0.52) and student engagement (M = 4.32, SD = 0.48) strongly correlate with innovation in teaching and research (r = .68, p < .01) and global collaboration (r = .74, p < .01). These findings indicate that institutions with advanced digital infrastructure and strong engagement strategies are more likely to participate in cross-border academic networks and interdisciplinary research. The NVivo 12 thematic analysis identified five major themes: (1) digital transformation in learning, (2) research innovation, (3) global collaboration, (4) institutional support, and (5) challenges of digital equity. Participants emphasized that digitalization has expanded access, improved pedagogical innovation, and strengthened global partnerships, though disparities in technological readiness remain across institutions. The integration of both analyses confirms that Europe’s higher education system is undergoing a holistic transformation technological, pedagogical, and institutional toward a globally connected and inclusive digital education ecosystem. These results underscore the importance of sustained digital investment and policy alignment to ensure equitable participation in global higher education.